Propuesta sobre beneficios del entrenamiento excéntrico en post quirúrgicos de ligamento cruzado anterior en la segunda fase de rehabilitación, en cuatro pacientes del centro de rehabilitación deportiva ángeles gym. Cali. (2006)
The intention of this investigation is to know the benefits the eccentric training in the rehabilitation of post surgical of crossed ligament previous in the second phase. The application of the investigation was made 4 people of the population because these fulfill the inclusion criterion, being a study that would be lent to make it in ampler populations Se made in the disciplinary center ANGELS GYM in where they enter approximately of 50 to 60 people with posquirúrgico of LCA to the year, this investigation is of type ballistic pro (quantitative - descriptive). All the patients made the same evaluation during the same period of study (second phase of rehabilitation). The results of this study threw disbalance muscular notable between the leg injured in not injured comparison to, which allowed acertadamente to focus the protocol of rehabilitation according to the physical characteristics of each patient.